2018
DOI: 10.1007/s10508-017-1140-0
|View full text |Cite
|
Sign up to set email alerts
|

Usage of the Terms Prostitution, Sex Work, Transactional Sex, and Survival Sex: Their Utility in HIV Prevention Research

Abstract: This article considers the terms prostitution, sex work, transactional sex, and survival sex, the logic of their deployment and utility to research concerned with people who are paid for sex, and HIV. The various names for paid sex in HIV research are invested in strategically differentiated positionings of people who receive payment and emphasize varying degrees of choice. The terminologies that seek to distinguish a range of economically motivated paid sex practices from sex work are characterized by an emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…As McMillan et al (2018) pointed out in their discussion of the links between sex work language choices and HIV transmission, "[a]gency is always circumscribed in some manner", leading them to argue for a "framework in which choice is conceptualized as a matter of contextual complexity and not imbued in notions of victimhood and culpability" (p. 1524). While clearly constrained within a coercive and stratified context, the workers we interviewed engaged or attempted to engage in many of the agentic activities documented by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…As McMillan et al (2018) pointed out in their discussion of the links between sex work language choices and HIV transmission, "[a]gency is always circumscribed in some manner", leading them to argue for a "framework in which choice is conceptualized as a matter of contextual complexity and not imbued in notions of victimhood and culpability" (p. 1524). While clearly constrained within a coercive and stratified context, the workers we interviewed engaged or attempted to engage in many of the agentic activities documented by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals may occasionally and opportunistically exact a fee or gift for a sexual service without perceiving themselves as someone who trades sex (Carael et al, 2006;Dennis, 2008;Harcourt & Donovan, 2005;Stoebenau et al, 2016). (For a discussion of various terms used for selling sex, see e.g., McMillan, Worth, & Rawstorne, 2018). Carael et al's (2006) estimates of commercial sex, based on 78 national representative household surveys and nine city based surveys, found that between 1% and 14% of men had paid for sex in the last 12 months, with large discrepancies between regions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, economic marginalization may increase potential for HIV exposure and infection by contributing to reliance on survival sex work, or exchanging sex for money, food, shelter, drugs, or other commodities [ 25 - 27 ]. Survival sex work has also been associated with coping-related substance use [ 12 , 13 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%